2005
DOI: 10.1254/jphs.fpj04045x
|View full text |Cite
|
Sign up to set email alerts
|

Atria Selective Prolongation by NIP-142, an Antiarrhythmic Agent, of Refractory Period and Action Potential Duration in Guinea Pig Myocardium

Abstract: Abstract. NIP-142 is a novel benzopyran compound that was shown to prolong the atrial effective refractory period and terminate experimental atrial fibrillation in the dog. In the present study, we examined the effects of NIP-142 on isolated guinea pig myocardium and on the Gprotein-coupled inwardly rectifying potassium channel current (acetylcholine-activated potassium current; I KACh ) expressed in Xenopus oocytes. NIP-142 (10 and 100 µM) concentration-dependently prolonged the refractory period and action p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
4
41
1
Order By: Relevance
“…In guinea-pig myocardium, we have shown that the acetylcholine-activated potassium current is present in the atrial myocardium in the absence of muscarinic receptor stimulation, and that NIP-142 prolongs action potential duration and effective refractory period through blockade of this current. 6,8) Such effect was not observed in the ventricle which may explain the atria-selective nature of NIP-142. Also in the case of the mouse atrium, NIP-142, as well as tertiapin, a peptide inhibitor of the acetylcholine-activated potassium channel, prolonged the late repolarization phase (Figs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In guinea-pig myocardium, we have shown that the acetylcholine-activated potassium current is present in the atrial myocardium in the absence of muscarinic receptor stimulation, and that NIP-142 prolongs action potential duration and effective refractory period through blockade of this current. 6,8) Such effect was not observed in the ventricle which may explain the atria-selective nature of NIP-142. Also in the case of the mouse atrium, NIP-142, as well as tertiapin, a peptide inhibitor of the acetylcholine-activated potassium channel, prolonged the late repolarization phase (Figs.…”
Section: Resultsmentioning
confidence: 96%
“…9) Measurement of the effective refractory period was performed by extracellular recording as previously described. 6) Drugs and Chemicals NIP-142 was synthesized by Nissan Chemical Industries (Tokyo, Japan). NIP-142 was added to the bath solution from a stock solution (100 mM) in 0.1 M HCl.…”
Section: Effect Of Nip-142 On Potassium Channel a A-subunitsmentioning
confidence: 99%
“…NIP-142 concentration-dependently prolonged APD only in the atrium. No significant changes in other action potential parameters, such as resting membrane potential, action potential amplitude and maximum rate of rise (Vmax), were observed (Matsuda et al, 2005). The effects of NIP-142 on refractory period and action potential were different from those of conventional class III agents.…”
Section: Effects Of Nip-142 On the Refractory Period And Action Potenmentioning
confidence: 98%
“…This compound had a slight effect on I K1 : about 40% inhibition was observed with 10 μmol/L NIP-142. The effect of NIP-142 on I KACh was examined in HEK293 cells (Matsuda et al, 2006) and Xenopus oocytes (Matsuda et al, 2005) expressing the GIRK1/GIRK4 channel. Concentration-dependent inhibition of the current was observed in both types of cells: the inhibitory effect was 8-10 times potent than those on IKur in both cells (Table 2).…”
Section: Effect Of Nip-142 On the Membrane Currentsmentioning
confidence: 99%
See 1 more Smart Citation